Photonic Frequency Conversion of OFDM Microwave Signals in a Wavelength‐Scale Optomechanical Cavity. Issue 11 (10th October 2021) - Mercadé, Laura; Morant, Maria; Griol, Amadeu; Llorente, Roberto; Martínez, Alejandro
Abstract: Optomechanical (OM) cavities enable coupling of near‐infrared light and GHz‐frequency acoustic waves in wavelength‐scale volumes. When driven in the phonon lasing regime, an OM cavity can perform simultaneously as a nonlinear mixer and a local oscillator—at integer multiples of the mechanical resonance frequency—in the optical domain. In this work, this property is used to demonstrate all‐optical frequency down‐ and up‐conversion of MHz‐bandwidth orthogonal frequency division multiplexed signals compliant with the IEEE 802.16e WiMAX wireless standard at microwave frequencies. To this end, a silicon OM crystal cavity (OMCC), supporting a breathing‐like mechanical resonance at f m ≈ 3.9 GHz and having a foot‐print ≈ 10 μ m 2, which yields frequency conversion efficiencies better than −17 dB in both down‐ and up‐conversion processes at mW‐scale driving power, is employed. This work paves the way toward the application of OMCCs in low‐power all‐photonic processing of digitally modulated microwave signals in miniaturized silicon photonics chips. Abstract : All‐optical frequency down‐ and up‐conversion of MHz‐bandwidth OFDM signals compliant with the IEEE 802.16e WiMAX wireless standard is demonstrated by using an optomechanical cavity. The cavity, built on a silicon chip and supporting a breathing‐like mechanical resonance at 3.9 GHz, performs simultaneously as nonlinear mixer and local oscillator when operated in the phonon lasing regime.